LISTENING COMPREHENSION DIFFICULTIES; A CASE STUDY OF EFL STUDENTS IN LISTENING CLASS - Asep Hardiyanto; Mutia Tanjung; Sigit Suharjono (Universitas Islam Negeri Alauddin Makassar, 2021)
Listening skill in English is one of the most important skills in communication and educational process. However, listening skill is a skill that is not easily mastered by all non-native speaker students. The students need to know and understand the difficulties in listening process. Therefore, the current study aims to investigate the difficulties faced by the students dealing with listening comprehension. This research is a descriptive qualitative research with case study approach that examines six students in third semester of the English education study program in Universitas Muhammadiyah Kotabumi with three different proficiency levels: low, moderate, and high level. The results of this study showed that students with low level faced difficulties with unfamiliar words (message content), speed of speech (speaker), and lack of vocabulary (listener). Then in moderate level students felt difficult in the speed of speech (speaker) and noises (physical settings). Meanwhile, students with high level faced difficulty with the long spoken text (message content), variety of accents (speaker) and noises (physical settings). It can be concluded that the listening comprehension difficulties encountered by the students at tertiary level are different depending on their proficiency in English. Therefore, the implication of the current study is that the lecturer need to consider the information revealed in this study in order to be able to overcome the difficulties faced by the students.